ANALISIS NILAI PENDIDIKAN KARAKTER DALAM NOVEL CINTA DI LAUHUL MAHFUZH KARYA DIAN ANANTARA - Indah Sekar Arum; Nanang Heryana; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study is to determine the value of character education contained in the novel Cinta di Lauhul Mahfuzh. The method used is a descriptive method. The results of the research in the novel have been found and classified in the novel Cinta di Lauhul Mahfuzh with character education values. The researcher found a group of data according to the existing theory, namely: the value of religious character with indicators of peace, steadfastness, and sincerity; nationalist character values with indicators of self-sacrifice and discipline; independent character values with indicators of hard work (work ethic), resilience (Banting), fighting power, professionalism, courage, and being a lifelong learner; the value of mutual cooperation with indicators of respect, inclusion, help, empathy, anti-discrimination, voluntary attitudes; integrity character values with indicators of honesty, love of truth, loyalty, moral commitment, responsibility, exemplary. The conclusion from the analysis of the value of character education in Dian Anantara's novel Cinta Di Lauhul Mahfuzh, which consists of religious character values, nationalist character values, independent character values, mutual cooperation character values, integrity character values.Keywords: Character, Education, Novel.